Antibacterial compounds from the roots of cratoxylum formosum spp. pruniflorum - Raksat,A. (Natural Product Communications, 2015)
Phytochemical investigation of the roots of Cratoxylum formosum spp. pruniflorum led to the isolation and identification of a new xanthone, namely cratopruniforone (1), together with 13 known compounds (2-14). Some of these more abundant compounds were evaluated for their antibacterial activities.